The Activity of the Social-Democratic Group ‘Yedinstvo’ in 1918-1919. / La actividad del grupo socialdemócrata ‘Yedinstvo’ en 1918-1919 - Kostiaev, Eduard V. (Utopía y Praxis Latinoamericana, 1970)
ABSTRACT G.V. Plekhanov was a cut above like-minded people of the “Yedinstvo” by his authority, the last stage of its existence remained practically unreported in the historical literature. It was established in the process of research that at that time activity of the group was crowned with an extremely curious historical paradox. As the supporters of Plekhanov, who was the founder of the National Social Democracy at his time, the “Reds” during the Civil War and stood on the other side of the barricades and supported Denikin, the “white” general and the worst enemy of their former party members, in 1919.RESUMEN A diferencia de G.V. Plekhanov fue un corte por encima de la gente de ideas afines del "Yedinstvo" por su autoridad, la última etapa de su existencia permaneció prácticamente sin ser reportada en la literatura histórica. Se estableció en el proceso de investigación que en ese momento la actividad del grupo se coronaba con una extremadamente curiosa paradoja histórica. Como partidarios de Plekhanov, quien fue el fundador de la Democracia Nacional Social en su tiempo, los "Rojos" durante la Guerra Civil se mantuvieron al otro lado de las barricadas y apoyaron a Denikin, el general "blanco" y el peor enemigo de sus antiguos miembros del partido, en 1919.